The role of monolingual dictionaries in second language vocabulary learning / Dayang Nur Salda Dharfifi Awang Salleh - Awang Salleh, Dayang Nur Salda Dharfifi (2015)
Vocabulary is seen as building blocks of a language. In order to master a language, the learner has to master the vocabulary. This study was intended to achieve the following objectives: (1) identify whether monolingual dictionaries assist the second language (SL) vocabulary learning, (2) to identify the factors influencing the use of monolingual dictionaries, and (3) to study the significance of the use of a monolingual dictionary in improving a vocabulary lesson. Descriptive statistics was used to collect the intended data. The data was collected through test, questionnaire, and interview. 60 Form Four students were selected based on their English PMR Grade to be part of this study. The sample was divided into two experimental groups. For the purpose of answering the questionnaire, 120 students from Form Four and Form Five were selected. The interview was done on five teachers and five students that have good English language background. The findings show that there is significant difference in the mean scores of the monolingual dictionary (MD) group and bilingual dictionary group. In addition, the most influential factor in choosing a dictionary is Learners5 Motivation and the least influential factor is Learners' Attitude. Moreover, the learning of second language vocabulary can be improved by using monolingual dictionary if the learners have a good awareness on the usage of the dictionary in their vocabulary learning process.